Social Media and Social Class in China: How Social Media Accelerates Class Consolidation and Social Stratification (Based on Socio-economic Indicators) (Journal of Advanced Research in Social Sciences, 2019)
This paper examines the development of Chinese social media platforms and corresponding socio-economic indicators. Applying Bourdieu's concepts of cultural capital and Fukuyama’s concepts of social capital, this paper analyzes various social media platforms and their impact on mobility across social classes in China. Government regulations are highly involved in Chinese social media platforms. Through measuring education, consumption, income inequality, social mobility, and other related socio-economic indicators, this paper argues that the emergence of social media platforms revolutionizes the traditional social class structure and results in a unique social stratification in China. Social media platforms empower upper classes, middle classes, and working classes differently. This paper's central proposition is that the rise of social media blurs boundaries between middle and working classes, but strengthens the upper classes' distinctiveness and further consolidates their capital. The models applied in this paper advances our understanding of the rise of social media and its role in advocating for social mobility while also its role in facilitating class consolidation.